2004
DOI: 10.1074/jbc.m411177200
|View full text |Cite
|
Sign up to set email alerts
|

ATP Effects on Insulin-degrading Enzyme Are Mediated Primarily through Its Triphosphate Moiety

Abstract: It has been reported previously that ATP inhibits the insulysin reaction (Camberos, M. C., Perez, A. A., Udrisar, D. P., Wanderley, M. I., and Cresto, J. C. (2001) Exp. Biol. Med. 226, 334 -341). We report here that with 2-aminobenzoyl-GGFLRKHGQ-ethylenediamine-2,4-dinitrophenyl as substrate, ATP and other nucleotides increase the rate >20-fold in Tris buffer. There is no specificity with respect to the nucleotide; however, ATP is more effective than ADP, which is more effective than AMP. Triphosphate itself w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
100
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(110 citation statements)
references
References 15 publications
8
100
0
Order By: Relevance
“…The IDE activity in cells may also be regulated by non-esterified fatty acids [34], nucleotide triphosphates [35] and post-translational modification [36]. In particular, ATP induces conformational and aggregation changes in IDE and inhibits insulin degradation in vitro [37].…”
Section: Discussionmentioning
confidence: 99%
“…The IDE activity in cells may also be regulated by non-esterified fatty acids [34], nucleotide triphosphates [35] and post-translational modification [36]. In particular, ATP induces conformational and aggregation changes in IDE and inhibits insulin degradation in vitro [37].…”
Section: Discussionmentioning
confidence: 99%
“…Camberos et al showed ATP inhibited insulin degradation [15]. However, it has also been reported that ATP can increase degradation of small peptides by IDE, while having little effect on insulin metabolism [16,17]. Whatever the effect on insulin degradation, ATP does induce a conformational change in IDE [16].…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme was maintained for 4 days under the above conditions before being used for crystallization trials employing the sitting drop vaporization method with Compact Clover plates (Emerald Biosystems). EDTA was used primarily to sequester any free Mg 2ϩ , which has been shown to reduce activation by ATP (21,23). The protein/ATP solution was mixed 1:1 with well solution containing 100 mM sodium citrate, pH 6.5, 100 mM ammonium acetate, and 20% PEG 4000, and crystals were grown at 22°C, usually accompanied by heavy precipitation.…”
Section: Preparation Of Ide Mutants-ratmentioning
confidence: 99%
“…In addition, IDE has been shown to be activated heterotropically by polyphosphate anions (21,22). In particular, ATP, other nucleotides, and triphosphate (PPP i ) activate the enzyme toward hydrolysis of certain substrates 100 -200-fold (21,23). More recently, it has been reported that IDE has ATPase activity, which is also dependent upon a site distinct from the active site (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation